Kualitas spermatozoa semen beku sapi Simental dengan suhu dan lama thawing yang berbeda - Kusumawati, E. D.; Krisnaningsih, A. T. N.; Romadlon, R. R. (Faculty of Animal Science, Universitas Brawijaya, 2016)
This study aims to investigate the quality of Simental frozen semen based on the temperatures and duration of thawing. The materials used in this study were frozen semen of Simental cattle. The study used a laboratory experiment using a completely randomized design (CRD) factorial with 6 treatments and 10 replications. The thawing temperatures were 37°C and 25°C and the durations of thawing were 7 seconds, 15 seconds and 30 seconds. The variables observed in this study were the motility, viability and abnormality of Simental frozen semen. The data were analyzed using analysis of variance (ANOVA). The difference in advanced test was done by using the smallest Real Difference Test. The results showed that the temperature and duration of thawing and the interaction of temperature and duration of thawing provide a highly significant difference (P <0.01) on motility, viability and abnormality of Simental frozen semen. The highest motility (45,5%) and viability (75,65%) were found on 37°C and during 30 seconds of thawing, and the lowest abnormality was 4,71%. This study concludes that the optimal thawing temperature and the lenght of thawing for Simental frozen semen is 37°C and 30 seconds respectively. Keywords:thawing, sperm, motility, viability, temperature, abnormality